2023
DOI: 10.1186/s13568-023-01556-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of ginsenoside compound K from American ginseng extract by fed-batch culture of Aspergillus tubingensis

Abstract: Compound K (C-K), one of the most bioactive ginsenoside, is produced by hydrolyzing the glycoside moieties of protopanaxadiol (PPD)-type glycosylated ginsenosides in the ginseng extract. To enhance the biotransformation of PPD-type ginsenosides in American ginseng extract (AGE) into C-K, the optimization of the feed type, concentration, and period for the carbon source sucrose and the reactant AGE was performed in fed-batch fermentation of Aspergillus tubingensis using a fermenter. The concentration (3.94 g/L)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As a result, vitamin D 3 bioconversion using different protein fractions of the crude cell lysate as well as studying different environmental factors influencing the bioconversion process, were carried out. Various recent studies have shown the value of the biotransformation processes of certain compounds using various natural lysates to produce valuable bioactive compounds (Taira et al 2018 ; Hou et al 2020a ; Zheng et al 2022 ; Song et al 2023 ) or biodegrade environmental toxic compounds or xenobiotics (Hou et al 2020b ; Zargar et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, vitamin D 3 bioconversion using different protein fractions of the crude cell lysate as well as studying different environmental factors influencing the bioconversion process, were carried out. Various recent studies have shown the value of the biotransformation processes of certain compounds using various natural lysates to produce valuable bioactive compounds (Taira et al 2018 ; Hou et al 2020a ; Zheng et al 2022 ; Song et al 2023 ) or biodegrade environmental toxic compounds or xenobiotics (Hou et al 2020b ; Zargar et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%